Risk Factors and Spatial-Temporal Analysis of Porcine Reproductive and Respiratory Syndrome Seroprevalence in China Before and After African Swine Fever Outbreak - Zhao, Pengfei; Wang, Chaofei; Cao, Wenjian; Fang, Rui; Zhao, Junlong (Frontiers in Veterinary Science, 2022)
Porcine reproductive and respiratory syndrome (PRRS) is an infected viral disease that harms the pig industry. Porcine reproductive and respiratory syndrome virus (PRRSV) is the causative agent characterized by reproductive failure and respiratory confusion. A cross-sectional investigation of PRRSV seroprevalence was performed in this study. 14134 serum samples were collected in pig farms without PRRSV vaccination from ten provinces and two cities in China from 2017 to 2021. PRRSV antibody was detected by Enzyme-linked immunosorbent assay (ELISA). The apparent and true prevalence of the PRRSV antibody was estimated and compared based on the copper-person method and Pearson chi-square test, respectively. Risk factors associated with serological status of pig farms were analyzed using univariate and multivariable logistic regression analysis. An automatic autoregressive integrated moving average (ARIMA) model procedure performed time-series analysis for PRRSV seroprevalence. Spatial clustering of high PRRSV seroprevalence was detected by SaTScan software. The total true PRRSV seroprevalence was 62.56% (95% CI: 61.74-63.37%). Furthermore, 286 out of 316 pig farms were positive for PRRSV antibodies. Pig farms without pseudorabies virus (PRV) were 3.475 (95% CI: 1.515-8.993) times more likely to be PRRSV antibody-positive than that with PRV. Identically, the possibility of pig farms being antibody-positive before the outbreak of African Swine fever (ASF) was 2.722 times after ASF. The odd ratio values of medium and large pig farms are 3.076 (95% CI: 1.005-9.498) and 6.098 (95% CI: 1.814-21.290). There was no particular fluctuation pattern for the prevalence of PRRSV in temporal analysis. Three significant clusters of high PRRSV seroprevalence were first detected in China, covering a time frame from January 2018 to September 2018, revealing high PRRSV prevalence before the outbreak of ASF. These findings show the epidemic situation and spatial-temporal distribution of PRRSV infection in China in recent years and help develop reasonable measures to prevent PRRSV infection.